Effect of Seagrass Density on Fish Abundance in the Seagrass Ecosystem of Pahawang Island, Lampung - Syahira, Nyimas Nanda; Sunaryo, Anna Ida; Aryawati, Riris; Isnaini, Isnaini; Hartoni, Hartoni (Jurnal Biologi Tropis, 2025)
Fish communities in seagrass ecosystems are known to play a vital role in maintaining coastal biodiversity due to the provision of essential habitat, food, and shelter. This study investigates the structure of fish communities associated with seagrass habitats and evaluates the influence of seagrass density on fish abundance in the coastal waters of Pahawang Island, Lampung. Field surveys were conducted in October 2025 at three purposively selected stations. Fish assemblages were sampled using gill nets, while seagrass density and coverage were quantified along transect–quadrat lines. Three seagrass species Enhalus acoroides, Thalassia hemprichii, and Halodule uninervis were identified, exhibiting spatial variability in coverage ranging from 18% to 44%. A total of 87 individual fishes, comprising nine species, were recorded, with Siganus spp. being the most abundant genus. Diversity, evenness, and dominance indices indicated a stable and well-balanced community structure. Statistical analyses revealed a significant positive relationship between seagrass cover and fish abundance, underscoring the ecological importance of seagrass meadows in supporting coastal fish populations. These findings provide critical insights for enhancing management and conservation strategies in the marine environment of Pahawang Island.